Considerations and Challenges in the Remdesivir COVID‐19 Pediatric Development Program. (4th October 2022) - Chan‐Tack, Kirk; Sampson, Mario; Earp, Justin; Arya, Vikram; Yao, Lynne; Alexander, John; Hausman, Ethan; Belew, Yodit; Birnkrant, Debra; Struble, Kimberly
Abstract: The US Food and Drug Administration is committed to the development of effective antiviral regimens for pediatric patients with coronavirus disease 2019 (COVID‐19), including infants and neonates. On April 25, 2022, the approved indication of remdesivir (RDV) was expanded to include pediatric patients 28 days and older and weighing at least 3 kg with positive results of direct severe acute respiratory syndrome coronavirus 2 viral testing, who are: Hospitalized, or Not hospitalized and have mild to moderate COVID‐19 and are at high risk for progression to severe COVID‐19, including hospitalization or death. Given the similar course of COVID‐19 in adults and pediatric patients, the approval of RDV for use in pediatric patients is supported by the safety and efficacy data from adequate and well‐controlled phase 3 trials in adults and adolescents; and by the safety and pharmacokinetic data from a single‐arm, open‐label, phase 2/3 pediatric clinical trial of 53 pediatric patients at least 28 days of age and weighing at least 3 kg with confirmed severe acute respiratory syndrome coronavirus 2 infection and mild, moderate, or severe COVID‐19. At the time of the April 25, 2022, approval action, the US Food and Drug Administration also revoked the emergency use authorization for RDV that previously covered this pediatric population. This article summarizes key issues and regulatory considerations involved in the RDV COVID‐19 pediatric development program, including the evolution of the emergency use authorization issued for RDV as results from registrational studies became available, and discusses lessons learned.